Market Force, Ecology, and Evolution - Farmer, J (2013)
In financial markets, an excess of buying tends to drive prices up, and an excess of selling tends to drive them down. This is called market impact. Based on a simplified model for market making, it is possible to derive a unique functional form for market impact. This can be used to formulate a non-equilibrium theory for price formation. Commonly used trading strategies, such as value investing, and trend following induce characteristic dynamics in the price. Although there is a tendency for self-fulfilling prophesies, this is not always the case; in particular, many value-investing strategies fail to make prices reflect values. When there is a diversity of perceived values, nonlinear strategies give rise to excess volatility. Many market phenomena such as trends and temporal correlations in volume and volatility have simple explanations. The theory is both simple and experimentally testable. Under this theory there is an emphasis on the interrelationships of strategies that makes it natural to regard a market as a financial ecology. A variety of examples show how diversity emerges automatically as new strategies exploit the inefficiencies of old strategies. This results in capital reallocations that evolve on longer time scales and cause apparent non-stationarities on shorter time scales. The drive toward market efficiency can be studied in the dynamical context of pattern evolution. The evolution of the capital of a strategy is analogous to the evolution of the population of a biological species. Several different arguments suggest that the time scale for market efficiency is years to decades.